Beyond attrition: advisor relationships, progress clarity, and laboratory switching in engineering doctoral programs - Bahnson, Matthew; Abane, Tabe Ako (Frontiers in Education, 2026)
IntroductionSeveral factors shape doctoral students’ decisions to leave their programs before completion. Among these, the quality of the advising plays a critical role. Yet, there remains limited understanding of how advisor relationships influence consequential decisions, such as early departure and lab change considerations in doctoral engineering students. This paper investigates the influence of advisor relationships on early departures and lab change considerations in doctoral engineering students.MethodsEngineering doctoral students from 26 top-ranked universities in the United States and 17 doctoral engineering disciplines responded to an online survey on departure considerations, advisor relationships, and lab change actions. In our sample (n = 269), fewer women (n = 108) participated compared to men (n = 121), with gender non-conforming individuals comprising a smaller proportion (n = 12), and 28 participants not self-identifying a gender. Linear regression was used to measure the association between advisor relationships and departure considerations, both with and without a master’s degree. Mediation tests were performed to assess the mediating effect of student’s ability to assess their progress to degree (progress assessment) on this relationship.ResultsOur results indicate that advisor relationships explained 12% of the variance in departure without a degree (R2 = 0.12, F (1, 267) = 36.85, p < 0.001) and with a master’s degree (R2 = 0.12, F (1, 267) = 35.66, p < 0.001). Progress assessment was statistically associated as a partial mediator of this relationship, with significant indirect effects (β = −0.05, p < 0.05) for departure with or without a master.DiscussionLow advisor relationship was associated with self-reported engagement in preparatory steps for early departure and research lab change considerations among doctoral engineering students. Conversely, negative advisor relationships are associated with increased self-reported engagement in steps leading to lab changes or departure considerations.